2015
DOI: 10.1177/0952076715610413
|View full text |Cite
|
Sign up to set email alerts
|

Localism and the third sector: New relationships of public service?

Abstract: Using interview and documentary empirical evidence from leaders of a local community group that took on the running of a leisure facility after its threatened closure by the local authority, this paper examines the relationship between third sector and state sector, the role of volunteers, the changing role of third sector organisations and the theoretical and practical limitations of 'localism' in making sense of these changes. It is suggested that localism is to be understood in relation to continuing centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
(53 reference statements)
0
7
0
1
Order By: Relevance
“…However, the NFWI (2013) study demonstrates that not only can the community-managed model enable a library's services to be tailored to the needs of the community, but it can also adapt more quickly as it faces less bureaucracy than it would have faced under public control; volunteers explained how being a part of the community meant they were often able to provide a more personal service. Fenwick and Gibbon (2016) identified the third sectora terrain outside of direct public or private controlto be distinctive in its sensitivity and closeness to users. One of the reasons cited for the success of Croxteth Community Library was its openness to, and extensive connections with, the local community, which is achieved both formally through the managing organisation and informally through staff and volunteers; for example, one member of staff had previously taught at local schools and so knew many of the users (Belger, 2014;Locality, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the NFWI (2013) study demonstrates that not only can the community-managed model enable a library's services to be tailored to the needs of the community, but it can also adapt more quickly as it faces less bureaucracy than it would have faced under public control; volunteers explained how being a part of the community meant they were often able to provide a more personal service. Fenwick and Gibbon (2016) identified the third sectora terrain outside of direct public or private controlto be distinctive in its sensitivity and closeness to users. One of the reasons cited for the success of Croxteth Community Library was its openness to, and extensive connections with, the local community, which is achieved both formally through the managing organisation and informally through staff and volunteers; for example, one member of staff had previously taught at local schools and so knew many of the users (Belger, 2014;Locality, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Localism Act 2012). Localism deemphasises the role of the state by transferring greater power and, in turn, responsibility to local government in how services are delivered (Fenwick & Gibbon, 2016). The potential for variation in who manages community sport facilities between different local authorities is a consequence of policy prioritising mixed sector service delivery and a blurring of sectoral lines, as outlined in Sporting Future (HM Government, 2015).…”
Section: Uk Community Sport: Policy and Governancementioning
confidence: 99%
“…Once transferred, CATs will still have to react to their market position (e.g. Fenwick and Gibbon 2016;Reid 2018).…”
Section: The Extent Of Community Asset Transfer Of Public Leisure Facmentioning
confidence: 99%
“…Similar benefits were identified in Aiken et al's (2011) survey of community organisations. Studies of CATs in leisure a few years after transfer have found the flexibility of management has allowed them to cut costs and to make the services they offer more responsive to local needs (Fenwick and Gibbon 2016;Aiken et al 2011;Findlay-King et al 2018b). The use of volunteers from the community as trustees and in operational roles brings the trust closer to the community to understand and respond to needs (Findlay-King et al 2018b).…”
Section: The Experience Post-transfermentioning
confidence: 99%